Biomineralization of Sr by the Cyanobacterium Pseudanabaena catenata Under Alkaline Conditions - Foster, Lynn; Morris, Katherine; Cleary, Adrian; Bagshaw, Heath; Sigee, David; Pittman, Jon K.; Zhang, Kejing; Vettese, Gianni; Smith, Kurt F.; Lloyd, Jonathan R. (Frontiers in Earth Science, 2020)
A non-axenic culture of Pseudanabaena catenata, a close relative of the bloom-forming cyanobacterium found in the high pH First Generation Magnox Storage Pond (FGMSP) at the Sellafield Nuclear Facility, was supplemented with 1 mM of SrCl2, to determine its effect on the fate of Sr. The addition of 1 mM Sr to the P. catenata culture resulted in ~16 % reduction in the overall growth of the culture (OD600nm) and a 21 % reduction in the concentration of chlorophyll-a (Chl-a) compared to those without Sr. The fate of Sr was assessed using a multi-technique approach. Inductively coupled plasma atomic emission spectroscopy (ICP-AES) showed that virtually all of the Sr was removed from solution, while extracellular biomineral precipitates were analysed using TEM analysis, and were shown to contain Sr, Ca and S using energy-dispersive X-ray spectroscopy (EDS) analysis. In addition, intracellular P-containing electron-dense features, likely to be polyphosphate bodies, were associated with the P. catenata cells and contained Sr. Bulk analysis of the cultures by X-ray diffraction (XRD) showed the presence of Ca-containing strontianite whilst EXAFS analysis showed the presence of strontium phosphate minerals. The presence of Sr associated with intracellular polyphosphate was unexpected, and contrasts with other model photosynthetic systems in the literature that have highlighted carbonate biominerals as the dominant sink for Sr. Understanding the fate of Sr within microorganisms associated with Spent Nuclear Fuel Ponds (SNFPs) is crucial to understanding the fate of radioactive 90Sr in such extreme environments, and could also suggest a potential remediation strategy for treatment of 90Sr contaminated waters from SNFPs and in contaminated aquatic systems.